Key issues for the design and development of mobile commerce services and applications. (23rd March 2005) - Andreou, Andreas S.; Leonidou, Costantinos; Chrysostomou, Chrysostomos; Pitsillides, Andreas; Samaras, George; Schizas, Christos
This paper suggests a new approach for developing m-commerce services and applications based on a scheme that divides m-applications into directory- and transaction-oriented classes, identifies mobile user requirements, and takes into consideration the constraints of current technologies for mobile and wireless computing. The efficacy of the proposed approach in a real scenario is discussed.